Slow Cooling at Higher Temperatures Recorded within High-P Mafic Granulites from the Southern Granulite Terrain, India: Implications for the Presence and Style of Plate Tectonics near the Archean–Proterozoic Boundary. (25th January 2019) - Chowdhury, Priyadarshi; Chakraborty, Sumit
Abstract: High-pressure metamorphism at relatively low to moderate temperature is considered to reflect the presence of plate margin processes. However, evidence of such metamorphism is scarce in the preserved archive of the Archean–early Proterozoic rock record. Extant geochronological studies show that parts of the Southern Granulite Terrain (SGT) of India experienced regional metamorphism from ∼2·49 to 2·44 Ga and thus provide an excellent natural laboratory to study the geodynamics that was prevalent within the first ∼50 Myr from the Archean–Proterozoic boundary. Here, we have constrained the pressure–temperature–time ( P – T – t ) evolution of a suite of mafic granulites from the Cauvery Shear System—a part of the SGT—that underwent the early Proterozoic regional metamorphism. Integrated results from mineral reaction histories, kinetically constrained thermobarometry and pseudosection analyses suggest that the studied mafic granulites, with a peak assemblage of garnet + aluminous clinopyroxene + plagioclase + rutile + quartz, were metamorphosed under high- P granulite (HPG) facies conditions of ∼800°C, 12–14 kbar. Subsequently, the rocks underwent simultaneous cooling and decompression, which is recorded by the formation of clinopyroxene + plagioclase coronae at ∼710°C, ∼10–11 kbar, and stabilization of amphibole in various modes at >580–620°C, ∼6–8 kbar. The constrained peak P – T values suggest that the studied rocks were buried significantly deeply below the Earth's surface at moderate temperatures and, at present, such metamorphic conditions are attained in orogenic plate margins. Consequently, the studied rocks suggest the presence of plate tectonics at the Archean–Proterozoic boundary. Furthermore, diffusion modeling of the preserved major element compositional zonations within garnet–clinopyroxene pairs shows that the mafic granulites cooled continuously, but relatively slowly, from peak- T to ∼650°C at rates varying between 5 and 30°C Ma –1 . Such a cooling history (during exhumation) at high temperatures indicates that high, perturbed crustal temperatures >600°C were sustained for tens of millions of years, which is uncommon in modern collisional settings. However, the recently proposed model of peeling-off (planar delamination) orogenesis involving hotter mantle during the Archean is consistent with the maintenance of high temperatures for longer durations. Therefore, we propose that the studied rocks preserve evidence for plate motions at the Archean–Proterozoic transition, but possibly with a style that is different from that operating at modern orogens.